The Effect of Duration of the Rivet Process on the Strength of Single Lap Joining - Priyahapsara, Istyawan (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Good airplane joining supports aircraft strength. The general joining process is using rivet as joining method. The parameter that affects the strength during the riveting process is the duration of the rivet head formation. The purpose was to determine the effect of the duration of rivet head formation on the quality of the joint. The research was carried out with the help of homemade tools, to ensure data consistency. The selected riveting duration is 3, 4, 5, 6 seconds. After connection, each connection was tested for strength through tensile testing and macro photo images from the joining. Results show that the 5-second duration provides the best connection with the tensile test results of 165 MPa. Based on the macro photo image, the 5 second rivet process produces the best connection because it produces the biggest rivet body so that it provides the greatest strength compared to the others.